Efektivitas Pembelajaran Mata Pelajaran Akidah Akhlak dengan Menggunakan Metode Tugas - Anggi Budi Setiawan; Benny Kurniawan; Fibriyan Irodati (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The research objectives are: (1) to describe the implementation of learning the Akidah Akhlak subject with the task method; (2) analyzing the effectiveness of learning the Akidah Akhlak subject by using the task method; and (3) knowing the supporting factors and inhibiting factors in learning Akidah Akhlak subjects in class XI Madrasah Aliyah Darussa'adah. This research is a qualitative research. The object of this research is the students of class XI Madrasah Aliyah Darussa'adah Petanahan Kebumen with a total of 74 students. The method used in this research is descriptive qualitative method. The data collected in the form of interviews, observations, and documentation. The data analysis carried out is qualitative data analysis. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Based on the results of the study, it can be concluded that: (1) The implementation of the Akhlak Akidah Learning Subject with the Assignment Method in class XI Madrasah Aliyah Darussa'adah has been going well and effectively; (2) The effectiveness of learning Akhlak Akidah Subjects with the Assignment Method in class XI Madrasah Aliyah Darussa'adah cannot be separated from several components, namely: (a) objectives, (b) educators, (c) students, (d) teaching materials, ( e) learning resources, (f) evaluation; (3) Supporting and Inhibiting Factors in Learning Akidah Akhlak Subjects in class XI Madrasah Aliyah Darussa'adah, namely: (a) supporting factors consisting of learning atmosphere, learning approach, student discipline, infrastructure, and learning media; (b) inhibiting factors consisting of physiological factors, psychological factors, and the environment.